Between the Cape Fold Mountains and the deep blue sea: Comparative phylogeography of selected codistributed ectotherms reveals asynchronous cladogenesis. (27th October 2022) - Myburgh, Angus Macgregor; Daniels, Savel Regan
Abstract: We compare the phylogeographic structure of 13 codistributed ectotherms including four reptiles (a snake, a legless skink and two tortoise species) and nine invertebrates (six freshwater crabs and three velvet worm species) to test the presence of congruent evolutionary histories. Phylogenies were estimated and dated using maximum likelihood and Bayesian methods with combined mitochondrial and nuclear DNA sequence datasets. All taxa demonstrated a marked east/west phylogeographic division, separated by the Cape Fold Mountain range. Phylogeographic concordance factors were calculated to assess the degree of evolutionary congruence among the study species and generally supported a shared pattern of diversification along the east/west longitudinal axis. Testing simultaneous divergence between the eastern and western phylogeographic regions indicated pseudocongruent evolutionary histories among the study taxa, with at least three separate divergence events throughout the Mio/Plio/Pleistocene epochs. Climatic refugia were identified for each species using climatic niche modelling, demonstrating taxon‐specific responses to climatic fluctuations. Climate and the Cape Fold Mountain barrier explained the highest proportion of genetic diversity in all taxa, while climate was the most significant individual abiotic variable. This study highlights the complex interactions between the evolutionary history of fauna, the Cape Fold Mountains and past climatic oscillations during the Mio/Plio/Pleistocene. The congruent east/west phylogeographic division observed in all taxa lends support to the conclusion that the longitudinal climatic gradient within the Greater Cape Floristic Region, mediated in part by the barrier to dispersal posed by the Cape Fold Mountains, plays a major role in lineage diversification and population differentiation.